RESEARCH OF THE UNACCEPTABLE DEFECTS CAUSES IN THE MANUFACTURE OF REINFORCING ROPE - Buzauova, Toty; Sivachenko, Leonid; Aizhambaeva, Saulekul; Toleubayeva, Shamshygaiyn; Zhuldyzai, Kaizait; Abdugaliyeva, Gulnur (Journal of Applied Engineering Science, 2022)
In the production of reinforcing ropes, the patenting of wire rods is carried out under the technical production regulations. Patenting is a consequence of isothermal treatment, in which the decomposition of supercooled austenite is carried out in the lower part of the temperature range of diffusion transformation. In the microstructure of patented steel, there should be no structures of prostate, bainite, and martensite. Such a structure has a combination of ductility as well as good deformability with high reduction ratios. In the production of ropes, failure to comply with these technical requirements can lead to serious consequences. The article examines the defects that have arisen in the production of reinforcing ropes. In the course of the study, on the surface where the wires broke, uneven colors, scratches, and small flaws were revealed. For microstructural analysis of the metal was used Microscope Altami MET 1C. As a result of the microstructural study of steel, areas with large-lamellar perlite were identified, which led to a wire break.
Keywords: reinforcing ropes, microstructural analysis of steel, heat treatment